PENGARUH KOMUNIKASI INTERPERSONAL PIALANG DAN KEPERCAYAAN TERHADAP KEPUASAN INVESTOR PADA PT. KONTAK PERKASA FUTURES - Ni Nyoman Nurani; Indah Apriliyani Santoso (Forum Manajemen STIMI Handayani Denpasar, 2020)
The purpose of this study was to determine the effect of broker interpersonal communication and trust in investor satisfaction at PT. Mighty Contact Futures. The population in this study are all investors of PT. Contact Mighty Future. The sampling technique used in this study was a sampling quota of 30 people. The type of data used is quantitative data and qualitative data. The data source used is primary data. Data collection techniques are observation, questionnaire and documentation. Data analysis techniques using multiple linear regression analysis, correlation analysis and determination analysis. The results showed interpersonal communication has a positive and significant effect on investor satisfaction at PT. Contact Mighty Bali Futures. Trust has a positive and significant effect on investor satisfaction at PT. Contact Mighty Bali Futures. There is a significant influence of interpersonal communication and trust together on investor satisfaction at PT. Contact Mighty Bali Futures. The magnitude of the influence of interpersonal communication and trust on investor satisfaction at PT. Bali Mighty Futures Contact is 57.3%.